2018
DOI: 10.3917/edd.312.0041
|View full text |Cite
|
Sign up to set email alerts
|

Non-linéarité entre inflation et croissance économique : quels enseignements pour la zone BEAC ?

Abstract: Distribution électronique Cairn.info pour De Boeck Supérieur. © De Boeck Supérieur. Tous droits réservés pour tous pays.La reproduction ou représentation de cet article, notamment par photocopie, n'est autorisée que dans les limites des conditions générales d'utilisation du site ou, le cas échéant, des conditions générales de la licence souscrite par votre établissement. Toute autre reproduction ou représentation, en tout ou partie, sous quelque forme et de quelque manière que ce soit, est interdite sauf accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The inflation rate ( π ) captured by the growth rate of the consumer price index (CPI). The CPI is one of the better proxies for prices than the GDP deflator in developing countries because a large proportion of spending is consumer spending (Mondjeli andTsopmo, 2017). The population growth rate (pop).…”
Section: Methodology and Datamentioning
confidence: 99%
“…The inflation rate ( π ) captured by the growth rate of the consumer price index (CPI). The CPI is one of the better proxies for prices than the GDP deflator in developing countries because a large proportion of spending is consumer spending (Mondjeli andTsopmo, 2017). The population growth rate (pop).…”
Section: Methodology and Datamentioning
confidence: 99%
“…Inflation reduces savings and discourages lending and borrowing because of high interest rates and the unprofitability of what could be done with the loan. Moreover, the work of Ndjokou and Tsopmo (2017) has shown that inflation at a certain threshold becomes counterproductive for economic agents. Yet firms need to finance themselves at low, optimal interest rates to adequately cover their investment and operating needs, in order to be able to create wealth for shareholders.…”
Section:  the Inflation Rate And Efficient Performancementioning
confidence: 99%
“…For external factors, we have, among other variables, the Inflation Rate (IR), the Oil Price Growth Rate (OPGR) and the BRVM Composite Stock Index Growth Rate (SIGR). These external factors have also been used in several works including those by Ndjokou and Tsopmo (2017), Echchabi and Azouzi (2017), Bagirov and Mateus (2019).…”
Section: Independent Variablesmentioning
confidence: 99%